The power of four : leadership lessons of Crazy Horse - Marshall, Joseph, 1945- (New York : Sterling, 2009)
Reveals the four principles that made Crazy Horse a dynamic and compassionate leader: know yourself, know your friends, know the enemy, take the lead.
Keywords: Crazy Horse, -- 1842-1877.; Leadership